ENT530: ZAS Fabrics business plan / Nur Syahirah Shahrin, Engku Aimi Engku Mohamad Nor Azlan and Zuraimah Zomadi - Shahrin, Nur Syahirah; Engku Mohamad Nor Azlan, Engku Aimi; Zomadi, Zuraimah (2017)
ZAS Fabrics is a partnership company which is located at Bandar Baru Bangi. Registered on 17 December 2017 and will operate on 17 Feruary 2017. ZAS Fabrics is focused on one type of fabric which is lace. Our products are from good quality materials and sell at reasonable price. Mission for ZAS Fabrics is make sure that our products will be known and satisfy the customer need also dedicated to consistently providing high customer satisfaction by rendering quality products with acceptable price or value relationship. We know that there are many other competitors in this industry but we will try our best in getting the customer trust and making our company well establish. We are also want to provide the highest and exclusive lace at affordable price to the customer. In the future, ZAS fabrics want to be the only company in providing the best and exclusive lace materials to the customers in Bangi The reason for ZAS Fabrics to choose this particular business is to expand the market on lace fabrics. Lace fabrics is known as beautiful, unique and people especially women love it. Usually they used lace fabrics as accessories on their clothes which can give the owner an elegant and mysterious look. Beside, ZAS Fabrics also want to expand the use of lace fabrics not only focus on clothes accessories but also as handicraft.